From Gut Dysbiosis to Skin Inflammation: Exploring the Hirschsprung's Disease-Psoriasis Link - Yildirim, Harun; Demir, Betul; Bakal, Unal; Ucer, Ozlem; Sevinc, Nur Sena; Yildirim, Ebru Aydin (Wiley, 2026)
Psoriasis is a skin disease characterized by erythematous and scaly lesions, influenced by genetic and environmental factors. Hirschsprung disease (HD) is a congenital disorder associated with gut microbiome dysbiosis, which can trigger inflammatory skin conditions. We report a case of psoriasis vulgaris in a male infant with HD whose skin lesions completely resolved after HD treatment. This case highlights a potential link between HD-related gut dysbiosis and psoriasis.
Keywords: dysbiosis; Hirschsprung disease; psoriasis